2022
DOI: 10.1021/acs.jproteome.1c00851
|View full text |Cite
|
Sign up to set email alerts
|

Balancing the Equation: A Natural History of Trimethylamine and Trimethylamine-N-oxide

Abstract: Trimethylamine (TMA) and its N-oxide (TMAO) are ubiquitous in prokaryote and eukaryote organisms as well as in the environment, reflecting their fundamental importance in evolutionary biology, and their diverse biochemical functions. Both metabolites have multiple biological roles including cell-signaling. Much attention has focused on the significance of serum and urinary TMAO in cardiovascular disease risk, yet this is only one of the many facets of a deeper TMA−TMAO partnership that reflects the significanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(10 citation statements)
references
References 340 publications
0
6
0
Order By: Relevance
“…In addition, LC supplementation elevates plasma TMAO level. Studies have shown that TMAO is a risk factor for the development of noncommunicable diseases, but whether it affects the health status of people without any chronic diseases is widely discussed (65)(66)(67), and needs further research.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, LC supplementation elevates plasma TMAO level. Studies have shown that TMAO is a risk factor for the development of noncommunicable diseases, but whether it affects the health status of people without any chronic diseases is widely discussed (65)(66)(67), and needs further research.…”
Section: Discussionmentioning
confidence: 99%
“…Based on our inability to detect methylphosphonate synthase ( mpnS ) genes or transcripts in our data, encoding the enzyme responsible for MPN synthesis [101], we propose that MPN is not produced endogenously by the sponge-associated community and rather likely sourced from the surrounding seawater. Conversely, the source of MeA may indeed be endogenous, deriving from the metabolic processing of TMA [102]. TMA can be produced from choline [103], glycine betaine [104] or carnitine [105].…”
Section: Resultsmentioning
confidence: 99%
“…Consistent with a Mediterranean dietary pattern, participants reported higher consumption of fish in the HMDA group. Urinary trimethylamine- N -oxide (TMAO) and its precursor trimethylamine are markers of fish consumption, particularly deep dwelling marine fish ( 77 ) but are also synthesized from bacterial degradation of dietary choline and carnitine found in red meats ( 56 , 77 ). Less commonly, urinary TMAO can also be related to legume intake ( 78 ).…”
Section: Discussionmentioning
confidence: 99%
“…Urinary and serum TMAO have been proposed as biomarkers of cardiovascular disease ( 79 ), however caution must be exercised in interpreting its role in dietary health. This is due to the fact that there are dietary sources of this metabolite, including fish ( 77 ), which is generally associated with alignment to a Mediterranean-style diet. In the current study, TMAO was positively associated with increased polyunsaturated fats, muesli intake, and nuts and legumes.…”
Section: Discussionmentioning
confidence: 99%